Performance of ECC Link Slab - Shoghi, Mohammad Javad (IRC, 2016)
The poor performance of durability and deformation of concrete bridges throughout the world is an increasingly large concern for highway transportation authorities. With decreasing budget allocations for infrastructure maintenance, rehabilitation, and replacement, the need for greater durability is apparent. The leaking at the expansion joints are a major source of multi-span bridge damages in those countries that most of the days during the year are rainy or snowy. One of the method which can reduce this problem is to place flexible link slab made of engineered cementitious composite (ECC) forming a joint free bridge. ECC actually is a type of high performance fiber reinforced cementitious composite with high durability and strain characteristic and multiple cracking reaction under deformation such as tension and flexure. In this project which is experimentally and analytically study on the fatigue behavior of ECC link slab. The requirements in terms of material, dimension and reinforcement detailing are considered.